Can a Strychnos species be used as antiulcer agent? Ulcer healing action from alkaloid fraction of Strychnos pseudoquina St. Hil. (Loganiaceae) - Bonamin, Flavia [UNESP]; Moraes, Thiago Mello [UNESP]; Kushima, Helio [UNESP]; Silva, Marcelo Aparecido [UNESP]; Rozza, Ariane Leite [UNESP]; Pellizzon, Claudia Helena [UNESP]; Bauab, Tais Maria [UNESP]; Machado Rocha, Lucia Regina [UNESP]; Vilegas, Wagner [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (Elsevier B.V., 2011)
Ethnopharmacological relevance: Strychnos pseudoquina St. Hil. (Loganiaceae) is one Brazilian native medicinal species described in the first edition of the Brazilian Official Pharmacopoeia in 1929. This medicinal plant, popularly known as quina-quina, quina-branca or casca aromatica was very commonly used in folk medicine in tea form obtained from the bark and/or leaves as tonic, antipyretic, antimalarial and mainly against diseases of the liver, spleen and stomach.Aim of the study: Previous study already characterized the gastroprotective action of this species The aim of the present study is to elucidate the mechanism of the healing process mediated by the methanolic extract (ME) and their enriched alkaloid fraction (EAF) from Strychnos pseudoquina in chronic gastric ulceration induced by 5% acetic acid in rats, an experimental model that accurately reflects human gastrointestinal disease.Material and methods: The ME and EAF was administered orally in a single dose (based on previously study of dose-response curve) for 14 days after chronic ulceration was induced in rats. The healing effect of ME and EAF was evaluated by macroscopic and morphometric analyses, immunohistochemical assay (PCNA and SOD) and anti-Helicobacter pylori effect was evaluated by in vitro assay.Results: Our results demonstrated that EAF significantly reduced border internal (42%) and external (38%) lesion area (mm(2)) by macroscopic analyses (P <0.05). Animals treated with EAF stimulated some proliferative factors by increasing the height of epithelial regenerative area and the expression of PCNA-positive nuclei. The number of vessels in gastric mucosa of rats treated with EAF reveals an expressive increase (4 times more than vehicle treatment) of vessels that stimulate cells proliferation in the healing region. These results suggest that the recovery of vascularization of the ulcerated area is involved in the healing action of alkaloid fraction of Strychnos pseudo quina. The MIC (minimum inhibitory concentration) of 75 mu g/ml from EAF showed an effective in vitro anti-Helicobacter pylori action of this fraction. EAF also was quite effective in the process of SOD release that is an important protective factor against bacterial agents. The efficacy of EAF was accomplished safely without presenting any alteration of toxicological parameters during 14 day of treatment.Conclusions: The expressive gastric healing effect by increasing cellular proliferation together with expression of SOD activity and antibacterial action against Helicobacter pylori confirm the efficacy of this species in heal gastric mucosa and these results are a important contribution to the knowledge of a crude drug presents at the Brazilian Official Pharmacopoeia since 1929. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Strychnos pseudoquina St. Hil.; Loganiaceae; Ulcer healing; PCNA; SOD; Angiogenesis